Timing of ejection fraction reassessment after sacubitril-valsartan initiation for indication to defibrillator implantation. A single center experience. (14th October 2021) - Carinci, V; Leci, E; Bugani, G; Greco, C; D'Angelo, C; Pecoraro, A; Casella, G
Abstract: Background: Sacubitril/Valsartan (SV) has recently been validated in the therapy of heart failure (HF) with reduced ejection fraction (EF). SV is effective on symptoms and heart remodeling. At the moment the best timing to EF assessment after SV initiation in order to proceed with defibrillator (ICD) implantation, it's unknown. Purpose: Evaluate the timing of improvement of EF after SV initiation in patients (pts) with systolic HF, candidates to primary prevention ICD implantation. Methods: We enrolled all consecutive pts candidates to primary prevention ICD implantation that underwent SV initiation from February 2018. We evaluated clinical and echo follow up (Fup). Results have been analyzed with paired T-test). Results: The study involved 61 pts (mean age 67±10 years, 71% male, ischemic cardiopathy 44%, mean time from diagnosis 31 months) with mean EF at enrollment 30±5% (ED vol 94 ml/m 2, ES vol 64 ml/m 2, severe MR 21%) and mean NYHA 3±0.6. After a mean Fup of 6 months mean EF increased to 37±7% (ED vol 80 ml/m 2, ES vol 51 ml/m 2, severe MR 8%, p<0.004), NYHA decreased to 2±0.6 (p<0.04). In 69% pts SV dosage reached 97/103 mg bid. 28 pts (45%) had first Fup at 3 months and showed already mean EF 34±6% and mean NYHA 1.6±0.6 (p<0.04). 26 pts (43%) had last Fup echo after 1 year (mean 17±10 months) and showed further EF little improvement (38.3±8%, p 0.05). Conclusions: After SV initiation in systolic HF, heart remodeling is already evident at 3 months Fup and better appreciable at 6 months Fup. Little non significant further EF improvement could be seen later. In our study best timing to decide for primary prevention ICD is likely between 3 and 6 months after SV initiation. Funding Acknowledgement: Type of funding sources: None.